Analisa Vegetasi Mangrove Di Desa Sebubus Kecamatan Paloh Kabupaten Sambas - Irwan Lovadi, Hambran, Riza Linda (Jurnal Protobiont, 2014)
West Kalimantan has large areas of mangroves including in Paloh District, Sambas Regency. This study analised community structure of mangrove areas in Paloh District. The research was conducted in January to February 2014. The combination of line and plot method was employed to complete the study. The research found 8 mengrove species belonging to 5 genera. Those genera are are Avicennia, Sonneratia, Rhizophora, Bruguiera and Excoecaria. Rhizophora mucronata (L.) has the highest Important Value Index with values ranging from 53.29 to ​​101.93. Diversity Index (H') of mangrove vegetation in the Sebubus Village was 1.721 and was classified as moderate. This indicates that mangrove ecosystem in the Sebubus Village was stabile community.